Separator for electrochemical device and electrochemical device comprising same

By using porous polymer substrate and polymer resin coatings with different solubility on the separator of lithium secondary batteries, combined with inorganic particles, the problem of high-pressure thermal deformation of the separator in silicon-based active material batteries is solved, and the battery resistance is improved Compressibility and heat resistance ensure battery performance.

CN119256444APending Publication Date: 2025-01-03LG ENERGY SOLUTION LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202480001958.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-05-03
Filing Date
2024-01-10
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

In lithium secondary batteries using silicon-based active materials, the separator is prone to deform due to high voltage and heat during the lamination process, resulting in hole deformation, dielectric breakdown voltage reduction and battery performance degradation.

Method used

Using a separator of a porous polymer substrate, the coating includes a high solubility first polymer resin and a low solubility second polymer resin, and a first coating and a second coating are formed on the surface of the porous polymer substrate. The second coating contains inorganic particles to adjust the solubility of the electrolyte and prevent pores from deforming.

Benefits of technology

It effectively prevents the deformation of pores in the porous polymer substrate, improves the compression resistance and heat resistance of the membrane, and avoids electrode short circuits and performance reduction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119256444A_ABST
    Figure CN119256444A_ABST
Patent Text Reader

Abstract

A separator for an electrochemical device includes a porous polymer substrate; a first coating layer provided on at least one surface of the porous polymer substrate and containing a first polymer resin having a first solubility in an electrolyte; and a second coating layer provided on the first coating layer and including a second polymer resin having a second solubility in the electrolyte and inorganic particles, in which the first solubility in the electrolyte is greater than the second solubility, and the separator is provided on a negative electrode containing a silicon (Si)-based active material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application is based on and claims the benefit of priority from Korean Patent Application No. 10-2023-0058002 filed on May 3, 2023 in the Korean Intellectual Property Office, the disclosure of which is incorporated herein by reference in its entirety.

[0002] The present disclosure relates to a separator for an electrochemical device and an electrochemical device including the separator. Background Art

[0003] The application range of secondary batteries such as lithium secondary batteries is gradually expanding to, for example, electric vehicles. The secondary battery generally generates electricity through a chemical reaction of lithium ions moving between a positive electrode material and a negative electrode material. The total capacity and voltage of the battery depend on the positive electrode material, while the negative electrode material is used to store and release lithium ions from the positive electrode.

[0004] On the other hand, while the positive and negative electrode materials represent the performance of the battery, the separator material can be said to be a key material related to the safety of the battery. In short, the separator is a thin film made of an insulating material that is used to separate the positive and negative electrodes in the battery so that the positive and negative electrodes do not contact each other. In addition, the separator has very fine pores that are invisible to the human eye, and lithium ions move between the positive and negative electrodes through the pores of the separator. In addition, when the temperature in the battery rises above a predetermined level, the separator is also used to prevent internal short circuits by closing the pores located on the surface of the separator, thereby blocking the movement of lithium ions.

[0005] Therefore, film substrates based on polymer resins having multiple pores are widely used as separators for electrochemical devices. Generally, electrode assemblies are manufactured by a lamination process in which the separator and the electrode are bonded by heat and pressure. As the heat and pressure applied in the process increase, the bonding force between the electrode and the separator increases. Summary of the invention

[0006] Technical issues

[0007] The present disclosure provides a separator for an electrochemical device disposed on a negative electrode containing a silicon (Si)-based active material, wherein the electrolyte solubility of a first polymer resin of a first coating layer and a second polymer resin of a second coating layer included in the coating layer is adjusted to suppress closed pores in a porous polymer substrate; and an electrochemical device comprising the separator.

[0008] Technical Solution

[0009] One embodiment of the present disclosure provides a separator for an electrochemical device disposed on a negative electrode containing a silicon (Si)-based active material. The separator comprises: a porous polymer substrate; a first coating layer disposed on at least one surface of the porous polymer substrate and containing a first polymer resin; and a second coating layer disposed on the first coating layer and containing a second polymer resin and inorganic particles. The solubility of the first polymer resin in the electrolyte is higher than the solubility of the second polymer resin in the electrolyte.

[0010] According to one embodiment of the present disclosure, the solubility parameter of the first polymer resin may be about 17 MPa. 1 / 2 Above and about 27 MPa 1 / 2 the following.

[0011] According to one embodiment of the present disclosure, the solubility parameter of the second polymer resin may be less than about 17 MPa. 1 / 2 or greater than about 27 MPa 1 / 2 .

[0012] According to one embodiment of the present disclosure, the first polymer resin may include one selected from the group consisting of polystyrene, polyethyl acrylate, polymethyl acrylate, polystyrene sulfide, polyethylene terephthalate, polyvinyl chloride (PVC), polyvinyl pyrrolidone (PVP), polyvinyl acetate (PVAc), polyacrylonitrile (PAN), polylactic acid (PLA), polyacrylic acid (PAA), and combinations thereof.

[0013] According to one embodiment of the present disclosure, the second polymer resin may include one selected from the group consisting of PVDF-HFP copolymer, PVDF-CTFE copolymer, PVDF-HFP-CTFE terpolymer, cyanoethyl polyvinyl alcohol, and combinations thereof.

[0014] According to one embodiment of the present disclosure, the separator may have a plurality of pores, the polydispersity index (PDI) of the porous polymer substrate may be about 2.5 or more and about 10 or less, and the average pore size of the porous polymer substrate may be about 20 nm or more and about 80 nm or less.

[0015] According to one embodiment of the present disclosure, the negative electrode may contain the silicon (Si)-based active material in an amount of about 50 wt % or more.

[0016] According to one embodiment of the present disclosure, the hardness of the negative electrode may be about 50 MPa or more and about 350 MPa or less.

[0017] One embodiment of the present disclosure provides an electrochemical device including a positive electrode, a negative electrode, an electrolyte, and a separator interposed between the positive electrode and the negative electrode.

[0018] According to one embodiment of the present disclosure, the solubility parameter of the first polymer resin may be about 17 MPa. 1 / 2 Above and about 27 MPa 1 / 2 the following.

[0019] According to one embodiment of the present disclosure, the electrolyte may include one selected from the group consisting of propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), fluoroethylene carbonate (FEC), and a combination thereof.

[0020] According to one embodiment of the present disclosure, a mixture obtained by mixing the diethyl carbonate (DEC) and the fluoroethylene carbonate (FEC) may be used as the electrolyte.

[0021] According to one embodiment of the present disclosure, the electrolyte may contain the diethyl carbonate (DEC) and the fluoroethylene carbonate (FEC) in a ratio of about 10:90 to 99:1.

[0022] Another embodiment of the present disclosure provides a method for manufacturing a separator for an electrochemical device, the separator being provided on a negative electrode containing a silicon (Si)-based active material, wherein the method includes coating a porous polymer substrate with a first polymer resin and a second polymer resin having different solubility in an electrolyte.

[0023] The solubility of the first polymer resin in the electrolyte may be higher than the solubility of the second polymer resin in the electrolyte.

[0024] The separator may include: a porous polymer substrate; a first coating layer provided on at least one surface of the porous polymer substrate and containing the first polymer resin; and a second coating layer provided on the first coating layer and containing a second polymer resin and inorganic particles.

[0025] A solubility parameter of about 17 MPa can be selected 1 / 2 Above and about 27 MPa 1 / 2 The following materials are used as the first polymer material.

[0026] The first polymer resin may be selected from the group consisting of polystyrene, polyethyl acrylate, polymethyl acrylate, polystyrene sulfide, polyethylene terephthalate, polyvinyl chloride (PVC), polyvinyl pyrrolidone (PVP), polyvinyl acetate (PVAc), polyacrylonitrile (PAN), polylactic acid (PLA), polyacrylic acid (PAA), and combinations thereof.

[0027] The second polymer resin may be selected from the group consisting of PVDF-HFP copolymer, PVDF-CTFE copolymer, PVDF-HFP-CTFE terpolymer, cyanoethyl polyvinyl alcohol, and combinations thereof.

[0028] Beneficial Effects

[0029] In a separator for an electrochemical device according to one embodiment of the present disclosure, the electrolyte solubility of the first polymer resin of the first coating layer and the second polymer resin of the second coating layer contained in the coating layer is adjusted so that deformation of the pores in the porous polymer substrate can be prevented even when a negative electrode containing a silicon (Si)-based active material is applied.

[0030] In an electrochemical device according to one embodiment of the present disclosure, the second coating layer containing the second polymer resin and inorganic particles is provided on the first coating layer containing the first polymer, so that even when a negative electrode containing a silicon (Si)-based active material is applied, deformation of pores in the porous polymer substrate can be prevented, and both compression resistance and heat resistance are improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 is a schematic diagram showing a separator for an electrochemical device and a negative electrode according to one embodiment of the present disclosure.

[0032] In a portion of the drawings, corresponding reference numerals indicate corresponding parts. The drawings presented are shown for simplicity and clarity and are not necessarily drawn to scale. For example, the dimensions of some elements in the drawings may be exaggerated relative to other elements to help improve the understanding of the various embodiments. In addition, elements of the prior art that are useful or substantially known in commercially feasible embodiments are sometimes not depicted so as not to obscure the subject matter of the various embodiments of the present invention. DETAILED DESCRIPTION

[0033] When it is described herein that a portion “includes” a certain component, unless specifically stated otherwise, this means that other components may be further included rather than excluded.

[0034] As used herein, "A and / or B" means "A and B, or A or B."

[0035] When it is described herein that components are provided “on” a component, unless specifically described to the contrary, this means that other components may be further disposed therebetween, and does not exclude that other components are disposed therebetween.

[0036] In this specification, the feature "having pores" means that an object contains a plurality of pores and allows gaseous and / or liquid fluids to pass through one surface of the object to reach another surface because the pores in the structure are connected to each other.

[0037] As used herein, the terms "about," "approximately," and "substantially" are used to mean a range of values ​​or degrees, or approximate values ​​thereof, taking into account inherent manufacturing and material tolerances, and are used to prevent an infringer from taking unfair advantage of the described content, where exact or absolute values ​​are mentioned to assist in understanding the present disclosure.

[0038] In the case of lithium secondary batteries, graphite is widely used as a negative electrode material, but the use of silicon (Si)-based negative electrode materials is expanding to improve the energy density of lithium secondary batteries. For example, the energy density of silicon negative electrode materials is about 10 times higher than that of graphite negative electrode materials. Therefore, when the silicon negative electrode material is applied, it has advantages in improving battery performance, such as increasing battery capacity and increasing charging speed.

[0039] On the other hand, in the secondary battery manufacturing process, the diaphragm and the electrode may undergo a stacking process in which relatively high temperature and pressure are applied. In this case, when a silicon negative electrode material is applied, since its hardness is higher than that of a general graphite-based negative electrode material, when the silicon negative electrode material and the diaphragm contact each other through the stacking process, the pores in the diaphragm are likely to be deformed. Therefore, when a high-hardness silicon negative electrode material is applied to the electrode assembly, it is necessary to ensure the compression resistance, insulation and heat resistance of the diaphragm, so that even when the diaphragm is in contact with the silicon negative electrode material, the pores in the diaphragm can be prevented from being deformed due to high pressure and heat during the stacking process.

[0040] For example, since the process speed has been recently increased for the purpose of improving productivity, the time for applying heat to the diaphragm has been shortened, so adhesion is ensured by increasing pressure. However, in this process, there is a concern that the diaphragm is deformed due to high pressure. In addition, during the lamination process, the thickness of the polymer film substrate is significantly reduced, and at the same time, the pores in the diaphragm may be severely damaged. As a result, there are problems such as a decrease in the dielectric breakdown voltage of the diaphragm and a decrease in the performance of the battery.

[0041] In particular, when silicon-based negative electrode active materials such as Si, SiO or Si alloys are used as negative electrode active materials for lithium secondary batteries, the volume expansion of the negative electrode is large, and the compression deformation of the diaphragm during charging and discharging due to the increase in internal pressure of the battery becomes more serious. In addition, the particle size, roughness and hardness of the silicon-based negative electrode active material are larger than those of the graphite negative electrode active material, and local damage may be caused to the diaphragm when stacked with the diaphragm. Therefore, the present disclosure provides a diaphragm with improved compression resistance, insulation and heat resistance to prevent pore deformation when the silicon-based negative electrode active material is applied.

[0042] In the present specification, the separator has a porous property including a plurality of pores, and serves as an ion-conducting barrier, blocking the electrical contact between the negative electrode and the positive electrode in an electrochemical device while allowing ions to pass therethrough.

[0043] In the following, reference will be made to Figure 1 The present disclosure is described in more detail.

[0044] One embodiment of the present disclosure provides a separator 100 for an electrochemical device provided on a negative electrode 200 containing a silicon (Si)-based active material. The separator 100 includes: a porous polymer substrate 110; a first coating layer 131 provided on at least one surface of the porous polymer substrate 110 and containing a first polymer resin; and a second coating layer 133 provided on the first coating layer 131 and containing a second polymer resin and inorganic particles. The solubility of the first polymer resin contained in the first coating layer 131 in the electrolyte is higher than the solubility of the second polymer resin contained in the second coating layer 133 in the electrolyte.

[0045] In a separator for an electrochemical device according to one embodiment of the present disclosure, even when a negative electrode containing a silicon (Si)-based active material is applied, deformation of the pores in the porous polymer substrate can be prevented by adjusting the electrolyte solubility of the first polymer resin of the first coating layer and the second polymer resin of the second coating layer contained in the coating layer.

[0046] Figure 1 Schematic diagram of a separator and a negative electrode for an electrochemical device according to one embodiment of the present disclosure. Figure 1 , a separator for an electrochemical device and a negative electrode according to one embodiment of the present disclosure will be described.

[0047] According to an embodiment of the present disclosure, the silicon (Si)-based negative electrode active material substantially contains an Si-based compound. Using the Si-based compound as a high-capacity negative electrode material because the Si-based compound reversibly occludes and releases lithium through a reaction with a lithium compound, and the theoretical maximum capacity is about 4200 mAh / g (9366 mAh / cc, specific gravity is 2.23), which is much larger than carbon-based materials.

[0048] According to an embodiment of the present disclosure, the Si-based compound may be selected from the group consisting of an Si / C composite, SiO2, SiO x (0 < x < 2), metal-doped SiO x (0 < x < 2), pure Si, a silicon (Si) nanostructure, and an Si alloy, or a mixture of two or more of the listed materials. Specifically, it may be a silicon-based oxide of SiOx (0 < x < 2). For example, x may be in the range of 0.1 ≤ x ≤ 1.2, or x may be 1.

[0049] For example, the Si / C composite undergoes a firing process in a state where carbon is combined with silicon or silicon oxide particles, so as to have a configuration in which the carbon material is coated on the particle surface or a configuration in which carbon is atomically dispersed within the silicon particles, and any configuration is possible without limitation as long as the carbon and silicon materials form a composite.

[0050] In addition, the configuration of the metal-doped SiO x (0 < x < 2) may be doped with one or more metals selected from the group consisting of Li, Mg, Al, Ca, and Ti.

[0051] When doped as described above, the irreversible SiO2 phase of the SiO x material is reduced or transformed into a metal silicate phase that is electrochemically inactive, which can improve the initial efficiency of the SiO x material, so it is more preferred. x The Si alloy is obtained by alloying Si with one or more metals selected from the group consisting of Zn, Al, Mn, Ti, Fe, and Sn, and may include, but is not limited to, for example, solid solutions, intermetallic compounds, and eutectic alloys with these metals.

[0052] Based on containing the silicon (Si)-based negative electrode active material, the negative electrode may further contain other negative electrode active materials such as graphite.

[0053]

[0054] ​Considering, for example, capacity, research and development of the above-mentioned silicon (Si)-based negative electrode active materials are still continuing, and when the silicon (Si)-based negative electrode active materials are applied as negative electrode active materials for lithium secondary batteries, there is a problem that due to the large volume expansion of the negative electrode, the compression deformation of the diaphragm becomes more serious during charging and discharging due to the increase in internal pressure of the battery. In addition, the particle size, roughness and hardness of the Si-based negative electrode active material are larger than those of the graphite negative electrode active material, and local damage may be caused to the diaphragm when stacked with the diaphragm. Therefore, it is intended to apply a diaphragm that can ensure both heat resistance and compression resistance to prevent deformation of the pores in the diaphragm.

[0055] According to one embodiment of the present disclosure, the porous polymer substrate 110 of the separator can be made of a polymer known as a porous polymer substrate for a lithium secondary battery, such as polyolefin, polyethylene terephthalate, polybutylene terephthalate, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenylene oxide, polyphenylene sulfide, and polyethylene naphthalate. In particular, the porous polymer substrate 110 can be made using a polyolefin as a base polymer. Examples of polyolefins include one or more of polyethylene, polypropylene, or polypentene.

[0056] A porous polymer substrate, for example, a polymer substrate having a plurality of pores produced using the polyolefin as a base is advantageous in terms of providing a closed-cell function at an appropriate temperature. In particular, when both polyethylene and polypropylene are included as the polyolefin, physical properties such as closed-cell properties and mechanical strength can be improved.

[0057] According to one embodiment of the present disclosure, the thickness of the porous polymer substrate may be about 1 μm to 100 μm. For example, the thickness of the porous polymer substrate may be about 10 μm or more and 95 μm or less, 15 μm or more and 90 μm or less, 20 μm or more and 85 μm or less, 25 μm or more and 80 μm or less, 30 μm or more and 75 μm or less, 35 μm or more and 70 μm or less, 40 μm or more and 65 μm or less, 45 μm or more and 60 μm or less, 50 μm or more and 65 μm or less, or 55 μm or more and 60 μm or less. The thickness may be, for example, about 1 μm to 30 μm or about 5 μm to 30 μm. By adjusting the thickness of the porous polymer substrate within the above range, the volume of the electrochemical device can be minimized, and the positive and negative electrodes can be electrically insulated.

[0058] According to one embodiment of the present disclosure, the porous polyolefin polymer substrate most commonly used as the porous polymer substrate may be manufactured as follows, but is not limited thereto.

[0059] The porous polyolefin polymer substrate is manufactured by a method comprising melting a polyolefin polymer and extruding it to form the polymer into a sheet, and then stretching the sheet polymer to generate microcracks, thereby forming micro gaps between lamellae, which are crystalline parts of the polymer (dry method). In addition, the separator can be manufactured by a method in which a polyolefin polymer is kneaded with a diluent at a high temperature to generate a single phase, and then the polymer material is phase-separated from the diluent during a cooling process, and then the diluent is extracted to form pores, and then the polymer material is stretched and heat-set (wet method).

[0060] According to one embodiment of the present disclosure, the electrochemical device separator includes a coating 130 disposed on at least one surface of the porous polymer substrate. For example, the electrochemical device separator includes a coating disposed on one or both surfaces of the porous polymer substrate. As described above, by including a coating disposed on at least one surface of the porous polymer substrate, the heat resistance and mechanical properties of the electrochemical device separator can be improved, and since the separator shrinks at high temperatures, the electrode can be prevented from short-circuiting.

[0061] According to one embodiment of the present disclosure, the separator includes a first coating 131 containing a first polymer resin. For example, the first coating may be located on the porous polymer substrate. Therefore, when the first coating is applied to the porous polymer substrate, the first polymer resin is located in the pores in the porous polymer substrate, so that the pores can be closed. As a result, even when the stacking process is performed by applying a negative electrode containing a Si-based negative electrode active material having a relatively high hardness, the deformation phenomenon in which the pores become smaller or closed is suppressed or avoided due to the first polymer resin located in the pores. Since the separator includes the first coating containing the first polymer resin as described above, a separator for an electrochemical device having improved compression resistance and heat resistance can be achieved even when the Si-based negative electrode active material is applied.

[0062] According to one embodiment of the present disclosure, the separator includes a second coating layer 133 disposed on the first coating layer and containing a second polymer resin and inorganic particles. For example, the second coating layer may be disposed on the first coating layer disposed on the porous polymer substrate. When the first polymer resin contained in the first coating layer is located in the pores of the porous polymer substrate and all or part of the first coating layer does not remain, the second coating layer may be positioned in contact with the porous polymer substrate. Since the separator includes the second coating layer disposed on the first coating layer as described above and containing the second polymer resin and inorganic particles, the heat resistance and mechanical properties of the separator can be improved, and since the separator shrinks at high temperatures, the electrode can be prevented from short-circuiting, and pores can be formed in the coating layer.

[0063] According to one embodiment of the present disclosure, the first polymer resin and the second polymer resin may each be in the form of particles. By using the first polymer resin and the second polymer resin each in the form of particles as described above, pores can be formed in the coating layer.

[0064] According to one embodiment of the present disclosure, each of the first polymer resin and the second polymer resin may be soluble. "Soluble polymer" means a polymer that is dissolved by a solvent and is not in the form of particles.

[0065] According to one embodiment of the present disclosure, the first coating layer may not include inorganic particles.

[0066] According to one embodiment of the present disclosure, the second coating may include a plurality of pores. Here, the pores refer to pores in the coating and are generated at positions different from the pores in the porous polymer substrate. For example, the coating may be a porous coating. For example, the coating may be a porous coating containing a plurality of pores. Since the coating includes a plurality of pores as described above, the coating allows lithium ions to pass through and current to flow while physically blocking the negative electrode and the positive electrode.

[0067] According to one embodiment of the present disclosure, the second coating layer may be formed by combining inorganic particles with the second polymer resin particles. The pores within the second coating layer may be caused by interstitial volumes, which are empty spaces between the inorganic particles.

[0068] According to one embodiment of the present disclosure, the inorganic particles contained in the second coating are not particularly limited, as long as the particles have electrochemical stability. That is, the inorganic particles that can be used in the present disclosure are not particularly limited, as long as they are within the operating voltage range of the applied electrochemical device (e.g., based on Li / Li+ 0 to 5 V) without oxidation and / or reduction reaction. For example, when inorganic particles having ion transport capability are used, performance improvement can be achieved by increasing the ion conductivity in the electrochemical device. In addition, when inorganic particles with a high dielectric constant (hereinafter referred to as "high-k inorganic particles") are used as the inorganic particles, the inorganic particles help to increase the degree of dissociation of electrolyte salts such as lithium salts in the liquid electrolyte, thereby improving the ion conductivity of the electrolyte. The inorganic particles may include high-k inorganic particles having a dielectric constant of about 5 or more or about 10 or more, inorganic particles having lithium ion transport capability, or a mixture thereof. For example, the inorganic particles may be one selected from the group consisting of: BaSO4, BaTiO3, Pb(Zr,Ti)O3 (PZT), Pb 1-x La x Zr 1-y Ti y O3 (PLZT, 0 <x<1,0<y<1)、Pb(Mg 1 / 3 Nb 2 / 3 )O3-PbTiO3 (PMN-PT), hafnium dioxide (HfO2), SrTiO3, SnO2, CeO2, MgO, Mg(OH)2, NiO, CaO, ZnO, ZrO2, SiO2, Y2O3, Al2O3, SiC, Al(OH)3, TiO2, aluminum peroxide, zinc tin hydroxide (ZnSn(OH)6), tin zinc oxide (Zn2SnO4, ZnSnO3), antimony trioxide (Sb2O3), antimony tetroxide (Sb2O4), antimony pentoxide (Sb2O5), boehmite (AlO(OH)) and combinations thereof. However, these are merely examples and the present disclosure is not limited thereto.

[0069] According to one embodiment of the present disclosure, the size of the inorganic particles is not limited, but can be about 40 nm or more and about 3 μm or less to form a coating having a uniform thickness and an appropriate porosity. For example, the size of the inorganic particles can be about 40 nm or more and 2.5 μm or less, 40 nm or more and 2 μm or less, 40 nm or more and 1.5 μm or less, or 40 nm or more and 1.0 μm or less. When the size of the inorganic particles satisfies the above range, the physical properties of the diaphragm can be easily adjusted because the dispersibility is maintained, the mechanical properties can be improved because the thickness of the coating is avoided from increasing, and the possibility of internal short circuits due to excessive pore size during battery charging and discharging is low.

[0070] According to one embodiment of the present disclosure, the coating layer may be formed on one side of the porous polymer substrate with a thickness of about 1 μm or more and 10 μm or less, and the thickness of the coating layer may be about 1 μm or more and 9 μm or less, 2 μm or more and 8 μm or less, 3 μm or more and 7 μm or less, 3 μm or more and 6 μm or less, or 3 μm or more and 5 μm or less. According to one embodiment, the coating layer may be coated on both sides of the porous polymer substrate with a thickness of 4 μm on one side.

[0071] According to one embodiment of the present disclosure, the thickness of the polymer substrate and / or the coating can be measured by using a contact thickness gauge. As a contact thickness gauge, for example, VL-50S-B manufactured by Mitutoyo Corporation can be used.

[0072] According to one embodiment of the present disclosure, the solubility of the first polymer resin in the electrolyte is higher than the solubility of the second polymer resin in the electrolyte.

[0073] For example, the first polymer resin refers to a polymer resin that is dissolved by the electrolyte when the electrolyte is injected into a battery shell equipped with an electrode assembly so that the electrode assembly is immersed in the electrolyte, and is ultimately dissolved by the electrolyte in the lithium secondary battery product. The polymer solution coated on the porous polymer substrate is manufactured by dissolving the first polymer resin soluble in the electrolyte in a solvent. Any liquid can be used as a solvent as long as the liquid can dissolve the first polymer resin, but when the solvent has an affinity for the polymer component of the porous polymer substrate, the solvent easily penetrates into the pores of the porous polymer substrate.

[0074] In addition, the second polymer resin refers to a polymer resin that is not dissolved or very little dissolved by the electrolyte when the electrolyte is injected into a battery shell equipped with an electrode assembly so that the electrode assembly is immersed in the electrolyte, and is ultimately not dissolved in large quantities by the electrolyte in the lithium secondary battery product. That is, since it is not necessary to dissolve the second polymer into the electrolyte, the second polymer resin can be interpreted as a polymer resin that is swollen by the electrolyte but not soluble in the electrolyte.

[0075] As described above, when the solubility of the first polymer resin in the electrolyte is adjusted to be higher than the solubility of the second polymer resin in the electrolyte, even when a negative electrode containing a silicon (Si)-based active material is applied, compression resistance and heat resistance can be improved by preventing deformation of the pores within the porous polymer substrate.

[0076] According to one embodiment of the present disclosure, the solubility parameter of the first polymer resin may be about 17 MPa. 1 / 2 Above and 27 MPa 1 / 2 For example, the solubility parameter of the first polymer resin may be about 18 MPa. 1 / 2 Above and 26 MPa 1 / 2 Below, 19 MPa 1 / 2 Above and 25 MPa 1 / 2 Below, 20 MPa 1 / 2 Above and 24 MPa 1 / 2 Below or 21MPa 1 / 2 Above and 23 MPa 1 / 2 By adjusting the solubility parameter of the first polymer resin to increase the electrolyte solubility, the compression resistance of the separator for an electrochemical device is improved.

[0077] According to one embodiment of the present disclosure, the solubility parameter of the second polymer resin may be less than 17 MPa. 1 / 2 or greater than 27 MPa 1 / 2 When the solubility parameter of the second polymer resin is adjusted so that the difference in solubility parameter between the second polymer resin and the electrolyte is relatively large, the particle shape can be maintained even under the electrolyte, and dissolution into the electrolyte can be prevented, so that the heat resistance and mechanical properties of the separator can be improved due to the second polymer resin and the inorganic particles, and the separator shrinks at a relatively high temperature, so that short circuit of the electrode can be prevented, and pores can be formed in the coating layer.

[0078] According to one embodiment of the present disclosure, the difference between the solubility parameter of the first polymer resin and the solubility parameter of the second polymer resin may be about 3 or more and 100 or less. The difference may be about 5 or more and 100 or less, or 7 or more and 100 or less.

[0079] According to one embodiment of the present disclosure, the electrolyte solubility parameter can be represented by the Hansen solubility parameter (HSP). That is, each material has an inherent solubility parameter value, and materials with similar solubility parameter values ​​dissolve or mix well with each other.

[0080] The Hansen solubility parameters were proposed by Dr. C. Hansen. In the Hansen solubility parameters, the degree of binding of materials is subdivided into the following three solubility parameters for consideration.

[0081] (1) Solubility parameter (δD) caused by non-polar dispersive bonds

[0082] (2) Solubility parameter (δP) due to polar bonds caused by permanent dipoles

[0083] (3) Solubility parameter (δH) due to hydrogen bonding

[0084] As such, the HSP can be used to accurately and systematically assess the solubility or miscibility of materials.

[0085] HSP = (δD, δP, δH), (J / cm 3 ) ½ (1)

[0086] δTot = (δD 2 +δP 2 +δH 2 ) ½ , (J / cm 3 ) ½ (2)

[0087] HSP is a vector with magnitude and direction in a space defined by three parameters. δTot represents the magnitude of the HSP vector. The basic unit for representing HSP is (J / cm 3 ) ½ . Such HSP values ​​can be calculated using a program called HSPiP (Hansen Solubility Parameters in Practice) developed by a research team led by Dr. Hansen who proposed the HSP. As described above, when two materials have similar HSV values, the materials dissolve each other well, wherein since the HSP is a vector, in order to determine that the materials are similar, the materials should be similar in terms of all three HSP elements and the size of the HSP. All materials have HSPs respectively, and by using the HSPs to compare and analyze the similarity differences, it is possible to predict whether the materials of interest will dissolve each other.

[0088] According to one embodiment of the present disclosure, the first polymer resin may include one selected from the group consisting of polystyrene, polyethyl acrylate, polymethyl acrylate, polystyrene sulfide, polyethylene terephthalate, polyvinyl chloride (PVC), polyvinyl pyrrolidone (PVP), polyvinyl acetate (PVAc), polyacrylonitrile (PAN), polylactic acid (PLA), polyacrylic acid (PAA), and combinations thereof. For example, the first polymer resin may be polyacrylic acid (PAA). As described above, when the first polymer resin is selected from the above group to form the first coating layer that dissolves into the electrolyte, even when a negative electrode containing a silicon (Si)-based active material is applied, compression resistance can be improved by preventing deformation of the pores in the porous polymer substrate.

[0089] According to one embodiment of the present disclosure, the second polymer resin may include one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP copolymer), polyvinylidene fluoride-chlorotrifluoroethylene copolymer (PVDF-CTFE copolymer), polyvinylidene fluoride-hexafluoropropylene-chlorotrifluoroethylene terpolymer (PVDF-HFP-CTFE terpolymer), cyanoethyl polyvinyl alcohol and a combination thereof. For example, the second polymer resin may be a PVDF-HFP copolymer and / or a PVDF-CTFE copolymer. As described above, when the second polymer resin is selected from the above group and the second coating containing the second polymer resin is formed that does not dissolve into the electrolyte, even when a negative electrode containing a silicon (Si)-based active material is applied, both compression resistance and heat resistance can be improved by preventing pore deformation in the porous polymer substrate.

[0090] According to one embodiment of the present disclosure, the commonly used acrylic polymer has a relatively high affinity for the electrolyte and substantially swells under the electrolyte even when cross-linked, so when the acrylic polymer is used alone, the polymer may swell (expand) and dissolve under the electrolyte. In contrast, the PVDF polymer has a large difference in the solubility parameter of the electrolyte, is conducive to maintaining the shape of the particles even under the electrolyte, and does not dissolve even when swollen under the electrolyte, thereby improving the compression resistance and heat resistance according to the present disclosure.

[0091] According to one embodiment of the present disclosure, the diaphragm may have a plurality of holes, the polydispersity index (PDI) of the porous polymer substrate may be about 2.5 or more and 10 or less, and the average pore size of the porous polymer substrate may be 20 nm or more and 80 nm or less. The polydispersity index of the porous polymer substrate is low, and the average pore size of the porous polymer substrate is small. When these ranges are met at the same time, compression resistance can be improved. For example, the polydispersity index (PDI) of the porous polymer substrate may be about 3.0 or more and about 9.5 or less, 3.5 or more and 9.0 or less, 4.0 or more and 8.5 or less, 4.5 or more and 8.0 or less, 5.0 or more and 7.5 or less, 5.5 or more and 7.0 or less, or 6.0 or more and 6.5 or less. When the polydispersity index is less than 2.5, there is a problem of reduced processability and reduced film uniformity, and when the polydispersity exceeds 10, there is a problem of reduced compression resistance.

[0092] In addition, for example, the average pore size of the porous polymer substrate may be about 25 nm or more and about 75 nm or less, 30 nm or more and 70 nm or less, 35 nm or more and 65 nm or less, 40 nm or more and 60 nm or less, or 45 nm or more and 55 nm or less. When the average pore size is less than 20 nm, there are problems of reduced air permeability and clogging of small pores by byproducts during battery charge and discharge, and when the average pore size exceeds about 80 nm, there are problems of uneven thickness of the separator, causing thickness deformation, and reduced compression resistance due to local thickness deformation.

[0093] According to one embodiment of the present disclosure, the average pore size of the porous polymer substrate can be calculated from the pore size distribution measured using a capillary flow porometer. For example, first, the diaphragm to be measured is wetted with a wetting agent such as a galwick solution, and then the air pressure on one surface of the substrate is gradually increased. At this time, when the applied air pressure becomes greater than the capillary attraction of the wetting agent present in the pores, the wetting agent blocking the pores is pushed out, and the pore size and distribution are measured based on the pressure and flow rate when being pushed out, thereby being able to confirm the average pore size.

[0094] According to one embodiment of the present disclosure, the content of the silicon (Si)-based active material in the negative electrode may be about 50% by weight or more. For example, the content may be 50% by weight or more and less than 100% by weight, 55% by weight or more and less than 95% by weight or less, 60% by weight or more and 90% by weight or less, 65% by weight or more and 85% by weight or less, 60% by weight or more and 80% by weight or less, or 65% by weight or more and 75% by weight or less. As described above, by adjusting the content of the silicon (Si)-based active material in the negative electrode, the energy density of the battery can be improved compared to when the graphite-based negative electrode active material is used alone.

[0095] According to one embodiment of the present disclosure, the hardness of the negative electrode may be about 50 MPa or more and about 350 MPa or less. For example, the hardness may be about 75 MPa or more and 325 MPa or less, 100 MPa or more and 300 MPa or less, 125 MPa or more and 275 MPa or less, 150 MPa or more and 250 MPa or less, or 175 MPa or more and 225 MPa or less. When the hardness is outside the above range, the pores of the separator are more likely to deform than when a graphite-based negative electrode active material is applied, and the energy density of the battery may be reduced.

[0096] According to one embodiment of the present disclosure, the hardness may be the indentation hardness (H IT ).

[0097] The indentation is one of the analysis methods of the mechanical properties of materials. It is an experimental method in which a diamond indenter of various shapes is pressed into the material, and then the indentation marks and the load during the indentation are compared and analyzed. The indentation test is a technique for measuring the fracture toughness or hardness of a material. In addition, the indentation test has recently been actively studied in various other directions, and the indentation test is also used as a research technique for, for example, the elastic-plastic behavior and residual stress state analysis of materials, adhesion experiments of thin films, and fracture characteristics and phase change analysis. In particular, when indentation is performed on fine materials such as the electrodes in the present disclosure, nanoindentation using an indenter to apply a load of less than N is applicable.

[0098] The hardness is obtained from an applied load-indentation depth curve obtained by continuously measuring the load applied by the indenter when the indenter is pressed into the surface of the electrode active material layer and the indentation depth during loading and unloading. For example, the hardness is calculated from the maximum load (Pmax) and the contact projection area A of the indenter when the indenter is pressed into the electrode active material layer by applying the maximum load (Pmax) by the formula Pmax / A.

[0099] Hardness is an indicator of the physical properties of the electrode active material layer. High hardness means that the electrode active material layer is less deformed due to external force. In other words, higher hardness means that the particles constituting the electrode active material are more firmly bound to each other, thereby having greater resistance to indentation. In contrast, lower hardness means that the particles constituting the electrode active material layer are more weakly bound to each other, thereby having less resistance to indentation.

[0100] According to one embodiment of the present disclosure, since the Si-based negative electrode active material has a higher hardness than the graphite negative electrode active material, the pores of the separator are likely to be deformed during an electrode assembly process.

[0101] In a membrane manufacturing process according to one embodiment of the present disclosure, a porous polymer substrate 110 may be provided, a first coating 131 may be formed on at least one surface of the prepared polymer substrate 110, and a second coating 133 may be formed on the first coating 131. According to one embodiment of the present disclosure, the method for forming the coating is, for example, as follows. First, a polymer solution is prepared by dissolving a binder resin in an appropriate organic solvent. For example, the solubility parameter of the solvent is similar to the solubility parameter of the binder polymer to be used, and its boiling point is lower than the boiling point of the binder polymer. This is to facilitate uniform mixing and subsequent removal of the solvent. Non-limiting examples of available solvents include acetone, tetrahydrofuran, dichloromethane, chloroform, dimethylformamide, N-methyl-2-pyrrolidone (NMP), cyclohexane, water or a mixture thereof. Next, inorganic particles are added to the prepared polymer solution and dispersed to prepare a porous polymer substrate 110. In the present disclosure, the content ratio of the inorganic particles to the binder is appropriately adjusted in consideration of the thickness, pore size and porosity of the coating of the present disclosure finally manufactured. Next, the first polymer material and the second polymer material are selected to produce a first coating slurry and a second coating slurry, respectively. Thereafter, the solubility of the selected first polymer material in the electrolyte is compared with the solubility of the selected second polymer material in the electrolyte.

[0102] As a result of the comparison, when it is determined that the solubility of the first polymer material in the electrolyte is higher than the solubility of the second polymer material in the electrolyte, the selected first polymer material is applied to prepare the first coating slurry. Thereafter, the first coating slurry containing the first polymer material is applied to at least one surface of the prepared porous polymer substrate 110 and dried to form the first coating 131 on the porous polymer substrate 110. When it is determined that the solubility of the first polymer material in the electrolyte is lower than the solubility of the second polymer material in the electrolyte, the process returns to the previous step and repeats the selection of the first polymer material and the second polymer material. Next, the selected second polymer material is applied to prepare the second coating slurry, and the prepared second coating slurry is applied to the first coating and dried to form the second coating.

[0103] The first coating and the second coating can be prepared in a manner separated from each other in the same manner as described above. However, the first coating and the second coating can be inseparable from each other, for example, they can be applied simultaneously to form a coating. In addition, the order of the above-mentioned preparation process can be appropriately modified, without being limited to the order. For example, even before preparing the porous polymer solution, a process of selecting the first polymer material and the second polymer material and comparing their solubility in the electrolyte can be performed, and the preparation of the first coating slurry and the second coating slurry to which the first polymer material and the second polymer material are applied before preparing the porous polymer solution can also be performed. In addition, the first coating slurry and the second coating slurry can be prepared independently at the same time or at different times, without being restricted by the order of the process.

[0104] According to one embodiment of the present disclosure, the method of applying the slurry to the surface of the substrate of the separator is not particularly limited to any method disclosed herein. For example, various methods such as dip coating, die coating, roller coating, comma roller coating or a combination thereof may be used.

[0105] According to one embodiment of the present disclosure, the drying process appropriately sets the temperature and time conditions to minimize the occurrence of surface defects in the organic / inorganic composite coating. For the drying, a drying auxiliary device such as a drying furnace or a hot air blower can be used within an appropriate range.

[0106] According to one embodiment of the present disclosure, the prepared separator is sandwiched between the positive electrode and the negative electrode containing the Si-based negative electrode active material, and is manufactured into an electrode assembly by a stacking process in which heat and / or pressure is applied to combine the separator with the negative electrode and the positive electrode. The stacking process can be performed by a rolling device including a pair of pressing rollers. That is, interlayer bonding can be achieved by stacking the negative electrode, the separator, and the positive electrode in sequence and placing them in the space between the pressure rollers. At this time, the stacking process can be performed by hot pressing.

[0107] One embodiment of the present disclosure includes an electrochemical device including a positive electrode, a negative electrode, and an electrolyte, and including a separator interposed between the positive electrode and the negative electrode.

[0108] In the electrochemical device according to one embodiment of the present disclosure, the second coating layer containing the second polymer resin and inorganic particles is provided on the first coating layer containing the first polymer resin. Therefore, even when a negative electrode containing a silicon (Si)-based active material is applied, the pores in the porous polymer substrate can be prevented from being deformed, thereby improving both compression resistance and heat resistance.

[0109] According to one embodiment of the present disclosure, the negative electrode comprises a negative electrode current collector and a negative electrode active material layer on at least one surface of the current collector. The negative electrode active material layer comprises a negative electrode material containing a Si-based negative electrode active material and a binder resin, and optionally comprises a conductive material as required. As the negative electrode active material, a silicon (Si)-based negative electrode active material can be used alone, or optionally used in combination with a carbon-based negative electrode active material such as graphite. The silicon (Si)-based negative electrode active material can be the same as described above.

[0110] According to one embodiment of the present disclosure, the content of the silicon (Si) active material may be about 50% by weight or more. For example, the content may be 50% by weight or more and less than 100% by weight, 55% by weight or more and less than 95% by weight, 60% by weight or more and less than 90% by weight, 65% by weight or more and less than 85% by weight, 60% by weight or more and less than 80% by weight, or 65% by weight or more and less than 75% by weight. As described above, by adjusting the content of the silicon (Si) active material in the negative electrode, the energy density of the battery can be improved compared to when the graphite negative electrode active material is used alone.

[0111] According to one embodiment of the present disclosure, the positive electrode comprises a positive electrode current collector, and comprises a positive electrode active material layer comprising a positive electrode active material, a conductive material and a binder resin on at least one surface of the current collector. The positive electrode active material may contain one or a mixture of two or more of the following: a layered compound, such as a lithium manganese composite oxide (e.g., LiMn2O4 or LiMnO2), a lithium cobalt oxide (LiCoO2) and a lithium nickel oxide (LiNiO2); a lithium manganese oxide, such as those represented by the formula Li1+xMn2-xO4 (wherein x is 0 to 0.33), LiMnO3, LiMn2O3 and LiMnO2; a lithium copper oxide (Li2CuO2); a vanadium oxide, such as LiV3O8, LiV3O4, V2O5 and Cu2V2O7; ... 1-x M x Ni-site lithium nickel oxide represented by O2 (wherein M = Co, Mn, Al, Cu, Fe, Mg, B or Ga, x = 0.01 to 0.3); represented by the chemical formula LiMn 1-x M x Lithium manganese composite oxide represented by Li2Mn3MO8 (wherein M = Co, Ni, Fe, Cr, Zn or Ta, x = 0.01 to 0.1); LiMn2O4 in which part of the Li in the chemical formula is replaced by alkaline earth metal ions; disulfide compounds; and Fe2(MoO4)3. For example, the positive electrode active material may be LiNi 0.8 Mn0.1 Co 0.1 O2.

[0112] According to one embodiment of the present disclosure, the conductive material may be, for example, one selected from the group consisting of graphite, carbon black, carbon fiber or metal fiber, metal powder, conductive whisker, conductive metal oxide, activated carbon and polyphenylene derivatives, or a mixture of two or more of these conductive materials. In addition, the conductive material may be, for example, one selected from the group consisting of natural graphite, artificial graphite, super-p, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, denka black, aluminum powder, nickel powder, zinc oxide, potassium titanate and titanium oxide, or a mixture of two or more of these conductive materials.

[0113] According to an embodiment of the present disclosure, as the binder resin, a polymer resin commonly used in electrodes in the art can be used. The non-limiting examples of such binder resins include, but are not limited to, polyvinylidene fluoride-to-hexafluoropropylene, polyvinylidene fluoride-to-trichloroethylene, polymethyl methacrylate, polyethylhexyl acrylate, polybutyl acrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, polyethylene-to-vinyl acetate, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA), polyacrylic acid (PAA), polyethylene glycol (PEG), polyacrylonitrile (PAN) and polyacrylamide (PAM).

[0114] A battery may be manufactured by placing the electrode assembly prepared as above in an appropriate case and injecting an electrolyte into the case.

[0115] According to one embodiment of the present disclosure, the solubility parameter of the electrolyte may be about 17 MPa. 1 / 2 Above and 27 MPa 1 / 2 For example, the solubility parameter of the electrolyte may be about 18 MPa. 1 / 2 Above and 26 Mpa 1 / 2 Below, 19 Mpa 1 / 2 Above and 25 Mpa 1 / 2 Below, 20 Mpa 1 / 2 Above and 24 Mpa 1 / 2 Below or 21 Mpa 1 / 2 Above and 23Mpa 1 / 2Below. In the case where the above range of the electrolyte solubility parameter is satisfied, a first polymer resin having a solubility parameter similar to the above solubility parameter is impregnated in the electrolyte and then dissolution is caused, and even when a negative electrode containing a silicon (Si)-based active material is applied, both compression resistance and heat resistance can be improved by preventing the pores in the porous polymer substrate from deforming. That is, a smaller difference between the solubility parameter of the electrolyte and the solubility parameter of the first polymer resin can make the solubility excellent. Therefore, the solubility parameter of the electrolyte can be similar to or the same as the solubility parameter of the first polymer resin.

[0116] According to one embodiment of the present disclosure, the electrolyte may be prepared by making the electrolyte have A + B - The salt of the structure is obtained by dissolving or dissociating in an organic solvent, wherein A + Contains alkali metal cations, such as Li + 、Na + , K + or a combination thereof, B - Contains anions such as PF6 - 、BF4 - , Cl - Br - ,I - 、ClO4 - 、AsF6 - 、CH3CO2 - CF3SO3 - 、N(CF3SO2)2 - 、C(CF2SO2)3 - or a combination thereof, the organic solvent is, for example, propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), ethyl methyl carbonate (EMC), γ-butyrolactone or a mixture thereof. For example, according to one embodiment, the electrolyte may include one selected from the group consisting of propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), fluoroethylene carbonate (FEC) and a combination thereof.

[0117] According to one embodiment of the present disclosure, a mixture of the diethyl carbonate (DEC) and the fluoroethylene carbonate (FEC) may be used as the electrolyte.

[0118] According to one embodiment of the present disclosure, the content ratio of propylene carbonate (PC) to dimethyl carbonate (DMC) of the electrolyte may be about 10:90 to 99: 1. For example, the content ratio may be about 20:80 to 98:2, 30:70 to 97:3, 40:60 to 96:4, 50:50 to 95:5, 60:40 to 94:6, 70:30 to 93:7, 80:20 to 92:8, or about 90:10.

[0119] One embodiment of the present disclosure provides a battery module including a battery containing the electrode assembly as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source. Specific examples of the device include, but are not limited to, a power tool driven by a battery motor, an electric vehicle such as an electric vehicle (EV), a hybrid electric vehicle (HEV), or a plug-in hybrid electric vehicle (PHEV), an electric motorcycle such as an electric bicycle (E-bike) or an electric scooter (E-scooter), an electric golf cart, and a power storage system.

[0120] Invention Mode

[0121] Hereinafter, the present disclosure will be described in detail with reference to examples. However, the embodiments according to the present disclosure can be modified into various other forms, and the scope of the present disclosure should not be interpreted as being limited to the following embodiments. The embodiments described herein are provided to more completely explain the present disclosure to those of ordinary skill in the art.

[0122] <Example>

[0123] The SV9 diaphragm blank (thickness: 9 μm, porosity: 46%, basis weight: 4.9 g / m) manufactured by Shanghai Energy Company was used. 2 , Gurley value: 70 sec / 100 cc) as the porous polymer substrate.

[0124] On the other hand, polyacrylic acid (PAA) (CK-702 manufactured by Dow Chemical Company) was used as the first polymer resin soluble in the electrolyte, and the first polymer resin was completely dissolved in solvent water at a concentration of 10 wt %, thereby preparing a polymer solution. The solubility parameter of the electrolyte of the first polymer resin was 22.4 MPa. 1 / 2 .

[0125] The prepared polymer solution was dip-coated on the porous polyethylene polymer substrate blank and dried at 65° C. to form a polymer coating layer.

[0126] Next, as the second polymer resin, PVDF-HFP (solef 21510 (HFP 15 wt%) manufactured by Solvay) and PVDF-CTFE (solef 32008 manufactured by Solvay) were dissolved in the solvent acetone. Then, as a dispersant, a cyano resin (CYR-301 manufactured by Amerisource) was dissolved in the solvent acetone to prepare a slurry. The solubility parameters of the second polymer resins 21510 and 32008 were 13.5 MPa, respectively. 1 / 2 and 15.1 MPa 1 / 2 .

[0127] Al2O3 with an average particle size of about 500 nm and boehmite particles with an average particle size of 300 nm were prepared as inorganic particles. Al2O3, boehmite, 21510, 32008 and CYR-301 were added to the solvent acetone in an amount of 15 wt % and mixed uniformly to prepare a final slurry with a weight ratio of Al2O3:boehmite:21510:32008:CYR-301=66.3:11.7:15.5:4.5:2.0.

[0128] The prepared slurry was coated on both sides of the above polymer coating layer in a thickness of 8 μm and dried at 45° C. to form an outer coating layer.

[0129] Cathode Manufacturing

[0130] The positive electrode active material (LiNi 0.8 Mn 0.1 Co 0.1 O2), a conductive material (carbon black), a dispersant and a binder resin (a mixture of PVDF-HFP and PVDF) were mixed with water in a weight ratio of 97.5:0.7:0.14:1.66 to prepare a slurry for a positive electrode active material layer, wherein the concentration of the remaining components except water was 50% by weight. Next, the slurry was applied to the surface of a thin aluminum film (10 μm thick) and dried to manufacture a positive electrode having a positive electrode active material layer (120 μm thick).

[0131] Negative electrode manufacturing

[0132] Silicon particles (M702 manufactured by Elkem), a PAM-based binder (BUH0452 manufactured by Arakawa), a conductive material (SFG-6L manufactured by Imerys), a conductive material (SWCNT) (Tuball dispersion manufactured by Ocsial), and a CMC dispersant (SWCNT, Ocsial, Tuball dispersion) were mixed with water at a weight ratio of 80:9.4:9.6:0.4:0.6 to prepare a slurry for a negative electrode active material layer, wherein the concentration of the remaining components other than water was 25 wt %. Next, the slurry was applied to the surface of a thin copper film (8 μm thick) and dried to prepare a negative electrode with a loading of 8 mAh / cm 2 The hardness of the negative electrode was measured to be 80 MPa.

[0133] Lamination process

[0134] The negative electrode and the positive electrode prepared as above and the separators of the examples and comparative examples were stacked so that each separator was interposed between the negative electrode and the positive electrode, and a lamination process was performed using a hot press at 70° C. and 5.2 MPa for 10 seconds to obtain an electrode assembly.

[0135] Electrolyte injection process

[0136] The electrode assembly obtained in the lamination process is inserted into a bag-type outer packaging material, and an electrolyte prepared by dissolving 0.5 M LiPF6 and 1.0 M LiFSI in a mixed solvent having a composition of DEC / FEC=90 / 10 (volume %) is injected into the bag-type outer packaging material to manufacture a lithium secondary battery.

[0137] <Comparative Example 1>

[0138] A lithium secondary battery was manufactured in the same manner as in Example, but the separator raw material was not coated with the solution of the first polymer resin.

[0139] <Comparative Example 2>

[0140] The separator blank is not coated with the solution of the first polymer resin. In addition, as the second polymer resin, a polymer having a solubility of 17 MPa in the electrolyte is used. 1 / 2 The above PVDF (KF9700 manufactured by Solvay) was dissolved in acetone to prepare a slurry. The solubility parameter of the PVDF as the second polymer resin was 19.2 MPa. 1 / 2 Then, as a dispersant, cyanoresin (CYR-301 manufactured by Amerigen Corporation) was dissolved in acetone, a solvent, thereby preparing a slurry.

[0141] Al2O3 with an average particle size of about 500 nm and boehmite particles with an average particle size of 300 nm were prepared as inorganic particles. Al2O3, boehmite, PVDF and CYR-301 were added to the solvent acetone in an amount of 15 wt % and mixed uniformly to prepare a final slurry with a weight ratio of Al2O3:boehmite:PVDF:CYR-301=66.3:11.7:20:2.0.

[0142] The prepared slurry was coated on both sides of the above polymer coating layer in a thickness of 8 μm and dried at 45° C. to form an outer coating layer.

[0143] <Comparative Example 3>

[0144] The SV9 diaphragm blank (thickness: 9 μm, porosity: 46%, basis weight: 4.9 g / m) manufactured by Shanghai Energy Company was used. 2 , Gurley value: 70 sec / 100 cc) as the porous polymer substrate.

[0145] On the other hand, polyacrylic acid (PAA) (CK-702 manufactured by Dow Chemical Company) was used as the first polymer resin soluble in the electrolyte, and the first polymer resin was completely dissolved in solvent water at a concentration of 10 wt %, thereby preparing a polymer solution. The solubility parameter of the electrolyte of the first polymer resin was 22.4 MPa. 1 / 2 .

[0146] In addition, as the second polymer resin, a 1 / 2 The above PVDF (KF9700 manufactured by Solvay) was dissolved in acetone to prepare a slurry. The solubility parameter of the PVDF as the second polymer resin was 19.2 MPa. 1 / 2 Then, as a dispersant, cyanoresin (CYR-301 manufactured by Amerigen Corporation) was dissolved in acetone, a solvent, thereby preparing a slurry.

[0147] Al2O3 with an average particle size of about 500 nm and boehmite particles with an average particle size of 300 nm were prepared as inorganic particles. Al2O3, boehmite, PVDF and CYR-301 were added to the solvent acetone in an amount of 15 wt % and mixed uniformly to prepare a final slurry with a weight ratio of Al2O3:boehmite:PVDF:CYR-301=66.3:11.7:20:2.0.

[0148] The prepared slurry was coated on both sides of the above polymer coating layer in a thickness of 8 μm and dried at 45° C. to form an outer coating layer.

[0149] <Comparative Example 4>

[0150] Polyacrylamide (PAM) (MP15 manufactured by Song Kang Ind Co., Ltd.) was used as the first polymer resin insoluble in the electrolyte, and the first polymer resin was completely dissolved in solvent water at a concentration of 10 wt % to form a polymer solution. The solubility parameter of the electrolyte of the first polymer resin was 13.5 MPa. 1 / 2 Then, the first polymer resin is coated on the same porous polymer substrate as in the example.

[0151] Next, as the second polymer resin, PVDF-HFP (solef 21510 (HFP 15 wt%) manufactured by Solvay) and PVDF-CTFE (solef 32008 manufactured by Solvay) were dissolved in the solvent acetone. Then, as a dispersant, a cyano resin (CYR-301 manufactured by Amerisource) was dissolved in the solvent acetone to prepare a slurry. The solubility parameters of the second polymer resins 21510 and 32008 were 13.5 MPa, respectively. 1 / 2 and 15.1 MPa 1 / 2 .

[0152] Al2O3 with an average particle size of about 500 nm and boehmite particles with an average particle size of 300 nm were prepared as inorganic particles. Al2O3, boehmite, 21510, 32008 and CYR-301 were added to the solvent acetone in an amount of 15 wt % and mixed uniformly to prepare a final slurry with a weight ratio of Al2O3:boehmite:21510:32008:CYR-301=66.3:11.7:15.5:4.5:2.0.

[0153] The prepared slurry was coated on both sides of the above polymer coating layer in a thickness of 8 μm and dried at 45° C. to form an outer coating layer.

[0154] <Comparative Example 5>

[0155] Polyacrylamide (PAM) (MP15 manufactured by Song Kang Ind Co., Ltd.) was used as the first polymer resin insoluble in the electrolyte, and the first polymer resin was completely dissolved in solvent water at a concentration of 10 wt % to form a polymer solution. The solubility parameter of the electrolyte of the first polymer resin was 13.5 MPa. 1 / 2 Then, the first polymer resin is coated on the same porous polymer substrate as in the example.

[0156] In addition, as the second polymer resin, a 1 / 2 The above PVDF (KF9700 manufactured by Solvay) was dissolved in acetone to prepare a slurry. The solubility parameter of the PVDF as the second polymer resin was 19.2 MPa. 1 / 2 Then, as a dispersant, cyanoresin (CYR-301 manufactured by Amerigen Corporation) was dissolved in acetone, a solvent, thereby preparing a slurry.

[0157] Al2O3 with an average particle size of about 500 nm and boehmite particles with an average particle size of 300 nm were prepared as inorganic particles. Al2O3, boehmite, PVDF and CYR-301 were added to the solvent acetone in an amount of 15 wt % and mixed uniformly to prepare a final slurry with a weight ratio of Al2O3:boehmite:PVDF:CYR-301=66.3:11.7:20:2.0.

[0158] The prepared slurry was coated on both sides of the above polymer coating layer in a thickness of 8 μm and dried at 45° C. to form an outer coating layer.

[0159] <Experimental example>

[0160] [PDI measurement]

[0161] PDI = (weight average molecular weight) / (number average molecular weight)

[0162] At this time, as the values ​​of the weight average molecular weight and the number average molecular weight, the values ​​obtained by cutting the separator into a predetermined size and performing gel permeation chromatography (GPC) analysis were used.

[0163] [Measurement of average pore size]

[0164] The pore size was measured using a capillary flow porometer (CFP method) to obtain the pore size distribution.

[0165] [Thinning rate after hot pressing]

[0166] The thickness of the diaphragm of the embodiment and the comparative example manufactured as described above was changed by pressing using a hot press, and then the thickness was measured. The thinning rate was calculated using the following formula. The pressing was performed under the conditions of 70°C, 5.2 MPa and 10 seconds. The thickness was measured using a thickness gauge (VL-50S manufactured by Mitutoyo Corporation).

[0167] Thinning rate = {(diaphragm thickness before hot pressing - diaphragm thickness after hot pressing) / diaphragm thickness before hot pressing} * 100

[0168] [Wet heat shrinkage measurement experiment]

[0169] The separator was cut into a piece of 5 cm x 5 cm, 1 g of the PC solution was injected into a bag having the piece, and then the bag was sealed, thereby preparing a sample. After the sample was left at a temperature of 135° C. for 30 minutes, the shrinkage rate of the separator was measured.

[0170] The shrinkage ratio is obtained as a result of marking two arbitrary points in each of the MD and TD directions of the sample and calculating the increase / decrease ratio of the gauge distance (the distance between the marked points) according to Formula 1 below.

[0171] (Formula 1) Shrinkage rate (%) = {(BA) / A} X 100

[0172] In Formula 1, A is the measured distance in the initial state before being placed at a high temperature, and B is the measured distance in the final state after being placed at a high temperature.

[0173] [Capacity retention measurement after 500 cycles at 25°C and 1 C / 1 C]

[0174] The battery manufactured by the above method was repeatedly charged and discharged at 25° C. at a charge and discharge rate of 1 C in the range of 2.5 V to 4.25 V, and the discharge capacity ratio after 500 cycles was calculated.

[0175]

[0176] In the above Table 1, it is confirmed that the wet heat shrinkage in Comparative Examples 1 and 2 is poor compared to Examples because the first polymer resin is not coated on the blank.

[0177] In the case of Comparative Example 2, it was confirmed that the battery capacity retention ratio was slightly improved compared with Comparative Example 1 because the solubility parameter of the coating layer was relatively similar to that of the electrolyte.

[0178] The solubility difference between the first polymer resin and the second polymer resin of the separator in Comparative Example 3 is smaller than that in the embodiment, and compared with the embodiment, Comparative Example 3 shows a tendency for the ion conductivity and long-term battery capacity retention rate of the electrolyte to deteriorate due to excessive dissolution in the electrolyte.

[0179] In the case of Comparative Example 4, the separator was coated with the first polymer resin and the second polymer resin both of which were insoluble in the electrolyte, and as a result, it was confirmed that the battery capacity retention rate of Comparative Example 4 was deteriorated compared with the Example and Comparative Examples 3 and 5.

[0180] In the case of Comparative Example 5, the separator has the following characteristics, in which the first polymer resin coated on the substrate is insoluble in the electrolyte, and the second polymer resin applied to the coating layer is relatively soluble in the electrolyte. However, it was confirmed that the battery capacity retention rate was deteriorated compared with the example because the solubility parameter of the second polymer resin applied in the coating layer was lower than the solubility parameter of the first polymer resin coated on the blank of the example, and thus the coating layer had poor dissolution characteristics in the electrolyte.

[0181] From the foregoing, it will be understood that various embodiments of the present disclosure are described herein for illustrative purposes, and various modifications may be made without departing from the scope and spirit of the present disclosure. Therefore, the various embodiments disclosed herein are not intended to be limiting, and the true scope and spirit are indicated by the claims.

[0182] [Explanation of symbols]

[0183] 100...Diaphragm

[0184] 110...Porous polymer substrate

[0185] 130...Coating

[0186] 131...First coating

[0187] 133...Second coating

[0188] 200...Negative

Claims

1. A diaphragm for an electrochemical device, the diaphragm comprising: porous polymer substrate; a first coating disposed on at least one surface of the porous polymer substrate and comprising a first polymer resin having a first solubility in the electrolyte; as well as a second coating layer disposed on the first coating layer and comprising a second polymer resin having a second solubility in the electrolyte and inorganic particles, wherein the first solubility in the electrolyte is greater than the second solubility, and The separator is provided on the negative electrode containing a silicon (Si) based active material.

2. The separator according to claim 1, wherein the solubility parameter of the first polymer resin is 17 MPa 1 / 2 Above and 27 MPa 1 / 2 the following.

3. The membrane according to claim 1, wherein the solubility parameter of the second polymer resin is less than 17 MPa. 1 / 2 or greater than 27 MPa 1 / 2 .

4. The separator according to claim 1, wherein the first polymer resin comprises one selected from the group consisting of polystyrene, polyethyl acrylate, polymethyl acrylate, polystyrene sulfide, polyethylene terephthalate, polyvinyl chloride (PVC), polyvinyl pyrrolidone (PVP), polyvinyl acetate (PVAc), polyacrylonitrile (PAN), polylactic acid (PLA), polyacrylic acid (PAA), and combinations thereof. 5 . The separator according to claim 1 , wherein the second polymer resin comprises one selected from the group consisting of PVDF-HFP copolymer, PVDF-CTFE copolymer, PVDF-HFP-CTFE terpolymer, cyanoethyl polyvinyl alcohol, and combinations thereof.

6. The diaphragm according to claim 1, wherein the diaphragm has a plurality of pores, The polydispersity index (PDI) of the porous polymer substrate is 2.5 or more and 10 or less, and The average pore diameter of the porous polymer substrate is 20 nm or more and 80 nm or less. 7 . The separator according to claim 1 , wherein the negative electrode contains the silicon (Si)-based active material in an amount of 50 wt % or more. 8 . The separator according to claim 1 , wherein the negative electrode has a hardness of 50 MPa or more and 350 MPa or less. 9 . An electrochemical device comprising a positive electrode, a negative electrode, an electrolyte, and the separator according to claim 1 interposed between the positive electrode and the negative electrode.

10. The electrochemical device according to claim 9, wherein the solubility parameter of the electrolyte is 17 MPa 1 / 2 Above and 27 MPa 1 / 2 the following.

11. The electrochemical device according to claim 9, wherein the electrolyte comprises one selected from the group consisting of propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), fluoroethylene carbonate (FEC), and combinations thereof. 12 . The electrochemical device according to claim 11 , wherein the electrolyte is used by mixing the diethyl carbonate (DEC) and the fluoroethylene carbonate (FEC). 13 . The electrochemical device according to claim 12 , wherein the electrolyte contains the diethyl carbonate (DEC) and the fluoroethylene carbonate (FEC) in a ratio of 10:90 to 99:1.

Citation Information

Patent Citations

  • Compound, method for producing compound, adhesive composition, and adhesive tape

    KR1020230058002A